Evaluating the value of intrapartum fetal scalp blood sampling to predict adverse neonatal outcomes: A UK multicentre observational study. (September 2019) - Al Wattar, Bassel H.; Lakhiani, Aarti; Sacco, Adalina; Siddharth, Aditi; Bain, Alexandra; Calvia, Alexandra; Kamran, Atiyah; Tiong, Bing; Warwick, Bethan; MacMahon, Caroline; Marcus, Diana; Long, Emma; et al.
Abstract: Objective: To evaluate the value of fetal scalp blood sampling (FBS) as an adjunct test to cardiotocography, to predict adverse neonatal outcomes. Study design: A multicentre service evaluation observational study in forty-four maternity units in the UK. We collected data retrospectively on pregnant women with singleton pregnancy who received FBS in labour using a standardised data collection tool. The primary outcome was prediction of neonatal acidaemia diagnosed as umbilical cord arterial pH < 7.05, the secondary outcomes were the prediction of Apgar scores<7 at 1st and 5th minutes and admission to the neonatal intensive care unit (NICU). We evaluated the correlation between the last FBS blood gas before birth and the umbilical cord blood and adjusted for time intervals. We constructed 2 × 2 tables to calculate the sensitivity, specificity, positive (PPV) and negative predictive value (NPV) and generated receiver operating curves to report on the Area Under the Curve (AUC). Results: In total, 1422 samples were included in the analysis; pH values showed no correlation (r = 0.001, p = 0.9) in samples obtained within an hour (n = 314), or within half an hour from birth (n = 115) (r=-0.003, p = 0.9). A suboptimal FBS pH value (<7.25) had a poor sensitivity (22%) and PPV (4.9%) to predict neonatal acidaemia with high specificity (87.3%) and NPV (97.4%). Similar performance was noted to predict Apgar scores <7 at 1st (sensitivity 14.5%, specificity 87.5%, PPV 23.4%, NPV 79.6%) and 5th minute (sensitivity 20.3%, specificity 87.4%, PPV 7.6%, NPV 95.6%), and admission to NICU (sensitivity 20.3%, specificity 87.5%, PPV 13.3%, NPV 92.1%). The AUC for FBS pH to predict neonatal acidaemia was 0.59 (95%CI 0.59–0.68, p = 0.3) with similar performance to predict Apgar scores<7 at 1st minute (AUC 0.55, 95%CI 0.51–0.59, p = 0.004), 5th minute (AUC 0.55, 95%CI 0.48–0.62, p = 0.13), and admission to NICU (AUC 0.58, 95%CI 0.52–0.64, p = 0.002). Forty-one neonates had acidaemia (2.8%, 41/1422) at birth. There was no significant correlation in pH values between the FBS and the umbilical cord blood in this subgroup adjusted for sampling time intervals (r = 0.03, p = 0.83). Conclusions: As an adjunct tool to cardiotocography, FBS offered limited value to predict neonatal acidaemia, low Apgar Scores and admission to NICU.